UNLOCKING GROWTH IN THE MUSLIM WORLD: FINANCIAL DEEPENING AND ECONOMIC DEVELOPMENT IN OIC COUNTRIES - Yasmin (SHACRAL: Shari'ah Economics Review Journal, 2025)
This article investigates the relationship between financial deepening and economic development in member countries of the Organisation of Islamic Cooperation (OIC) using a two-way fixed effects panel regression with data from the World Bank. The dependent variable is real GDP per capita, while the main variable of interest is domestic credit to the private sector as a percentage of GDP, controlling for trade, investment, inflation, government expenditure, FDI, and unemployment. The results show that financial deepening has a positive and statistically significant effect on income, supporting the view that robust financial intermediation remains a key engine of growth in the Muslim world. The effects of other macroeconomic controls are more context-specific and reflect the persistent heterogeneity of OIC economies. The study highlights the importance of strengthening prudent, inclusive, and well-regulated financial systems to promote sustainable development in OIC member states.